(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Information is presented on the types of inheritance of hypertension in children, a description of monogenic forms of pathology is given, modern results of studies on the adhesion of hypertension, including in children with different chromosomal loci, are presented. An extensive comparative analysis of the results of studies on the association of the M235T polymorphism of the AGT gene with essential arterial hypertension of childhood and with hypersensitive arterial hypertension was carried out. It is shown that these results can be influenced by additional factors (ethnic, geographical, etc.), which makes it necessary to achieve a maximally homogeneous sample for the study with clear selection criteria when conducting such a genetic analysis.